Structural Evolution and Ionic Conductivity of Al2O3-Doped LLZO via Single Heat Treatment - Yuniarti, Endah; Priyono, Slamet; Sindhu Hendradjaja, Simon; Setiawan, Jan; Prijono, Kusdi; Femlee R, Brity (Jurnal Ilmu Fisika, 2025)
This study investigates the synthesis via solid state reaction and characterization of Li₇La₃Zr₂O₁₂ (LLZO) as a solid electrolyte doped with Al₂O₃ using a one-step heat treatment (sintering at 900°C for 4 hours). Samples were prepared with doping variations; pure LLZO (0Al-LLZO), 0.25Al-LLZO, and 0.5Al-LLZO, based on the formula  with x = 0, 0.25, and 0.5, and were mixed using ball milling for 4 hours at 25 Hz. XRD and Rietveld refinement confirmed the formation of a dominant tetragonal Li₇La₃Zr₂O₁₂ phase alongside minor secondary phases. Grain sizes ranged from 1.2 to 1.3 µm, and densification improved with increasing Al content. The 0.25Al-LLZO sample exhibited the highest ionic conductivity of 2.83 × 10⁻⁹ S/cm at room temperature, representing a 2.96-fold increase over undoped LLZO. These results indicate that Al doping significantly enhances structural stability and Li-ion transport in LLZO electrolytes processed at moderate temperatures.